Three dimensional numerical analysis of hemodynamic of stenosed artery considering realistic outlet boundary conditions. (March 2020) - Bit, Arindam; Alblawi, Adel; Chattopadhyay, Himadri; Quais, Qurratul Ain; Benim, Ali Cemal; Rahimi-Gorji, Mohammad; Do, Hoang-Thinh
Highlights: The outlets LSA and LCCA greatly influence the flow dynamic structure within the stenosed aortic arch. Severe stenoses in downstream was found to introduce secondary stenoses on the wall of inferior section of aortic arch. Outlet boundary conditions are equally significant while evaluating secondary-stenoses distribution throughout the diseased section, its upstream section, and down-stream section. Abstract: Background and objective: Mortality rate increases globally among which one third is due to diseased blood vessels. Due to late diagnoses of the disease in vessels (severe stenoses), qualitative and rapid assessment becomes difficult. Earlier assessment of stenoses can lead to formulation of effective treatment protocol. It is often found that proliferation of secondary stenoses at downstream of a stenosed vessel depends on the degree of severity of primary stenoses. Numerical investigation of flow dynamics of blood in such condition helps in prediction of distributed field of secondarystenoses. This investigation also requires consideration of rigorous boundary conditions at inlet and outlet of defined flow domain. Methods: Patient-specific geometry of aortic arch with stenoses in descending aorta was considered for numerical estimation of biofluid dynamics. Boundary conditionsat inlet and outlet were extracted from time-resolved pulsed Doppler Ultrasound imaging at appropriate sections of the vessel. Womersley inlet flux was considered. Flow parameters like wall shear stress, oscillatory shear index, etc. were evaluated at upper and lower aortic arch of the vessel at different combinations of boundary conditions at inlet and four outlets respectively. Results: Effect of outlet boundary conditions were acknowledged for the progression of secondary stenoses. Severity of primary stenoses was found influencing the progression of secondary stenoses. It was found that the outlets Left Subclavian Artery and Left Common Carotid Artery greatly influence the flow dynamic structure within the stenosed aortic arch. Simultaneously, lower wall of aortic-arch had shown more affinity for secondary stenoses progression. Conclusion: Aortic arch is a vital anatomical region of circulatory system which is vulnerable to progression of secondary stenoses in presence of primary stenoses in ascending or descending aorta. It also drives the author to speculate the influence of anurysm in descending aorta on this landmark of aortic arch.